Perilaku Remaja Putri Mengonsumsi Tablet Tambah Darah: Studi Kualitatif Di Smk An-Nuriyah Jakarta Tahun 2021 - Haerani, Alfiana Riedha; Febrianti, Febrianti (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Program of iron tablet supplementation to female adolescent in schools has conducted to overcome the problem of anemia. It was found that at SMK An-Nuriyah Jakarta in November 2020 only 41.7% of female adolescent consumed iron tablets, while the coverage of iron tablet supplementation was already 100%. This study was conducted to know behavior and perceptions behind the behavior of the female at the school in consuming iron tablets. The study used a qualitative approach and thematic analysis, conducted from October 2020 to August 2021 at SMK An-Nuriyah Jakarta. Data was obtained from 5 females as key informants, 4 parents and 1 school health unit teacher as supporting informants. All the key informants in this study had received 60 tablets of iron tablets from the school and consumed them. Two types of behavior were found in consuming iron tablets: drinking according to the rules and not according to the rules. Those who did not drink according to the rules, did not drink iron tablets regularly once a week outside the menstrual period and or did not drink once a day during menstruation period. Some of the informants who did not consume according to the rules felt that they were not threatened by the dangers of anemia because they did not have good knowledge about the impact of anemia. There were also those who felt threatened by the dangers of anemia but did not have good self-efficacy to face obstacles in drinking iron tablets. It was recommended to the community health center and the school to increase students' knowledge of the impact of anemia on the future of young women during pregnancy and childbirth. In addition, there should be peer counselors to increase the girls’ self-efficacy in overcoming the obstacles in consuming iron tablets. Keywords: Anemia, Consumption of iron tablets, Health Behavior, Female Adolescent AbstrakProgram Pemberian Tablet Tambah Darah (TTD) dilaksanakan pada remaja putri di sekolah untuk mengatasi masalah anemia. Ditemukan di Sekolah Menengah Kejuruan (SMK) An-Nuriyah Jakarta pada bulan November 2020 hanya 41,7% remaja putri mengonsumsi TTD, meskipun cakupan pemberian TTD di sekolah sudah 100%. Penelitian ini dilakukan untuk mengetahui perilaku dan persepsi yang melatarbelakangi perilaku remaja putri dalam mengkonsumsi TTD pada SMK tersebut. Penelitian dilakukan dengan pendekatan kualitatif menggunakan analisis tematik, dilakukan pada Oktober 2020 sampai Agustus 2021 di SMK An-Nuriyah Jakarta. Data diperoleh dari 5 remaja putri sebagai informan utama, 4 orang tua dan 1 orang guru Usaha Kesehatan Sekolah (UKS) sebagai informan pendukung. Semua informan utama dalam penelitian ini memperoleh TTD dari sekolah sebanyak 60 tablet dan mengkonsumsinya. Ditemukan dua perilaku dalam mengkonsumsi TTD yaitu: meminum sesuai aturan dan tidak sesuai aturan. Yang meminum tidak sesuai aturan meminum TTD tidak rutin seminggu sekali diluar masa haid dan atau tidak minum sehari sekali pada saat haid. Informan yang meminum tidak sesuai aturan ada yang merasa tidak terancam oleh bahaya anemia karena tidak memiliki pengetahuan yang benar mengenai dampak anemia. Ada juga yang merasa terancam akan bahaya anemia tetapi tidak memiliki self efficacy yang baik untuk menghadapi kendala dalam minum TTD. Disarankan kepada puskesmas dan pihak sekolah untuk meningkatkan pengetahuan siswa terhadap dampak anemia pada masa depan remaja putri, ketika hamil dan melahirkan. Selain itu, perlu ada konselor sebaya untuk meningkatkan self efficacy remaja putri yang belum mampu mengatasi kendala dalam mengkonsumsi TTD.Kata kunci: Anemia, Konsumsi TTD, Perilaku Kesehatan, Remaja Putri